LANDASAN FILOSOFIS ILMU DALAM PERSPEKTIF BARAT DAN ISLAM: TINJAUAN ONTOLOGI DAN EPISTEMOLOGI - Indriana Silva, Melinda; Nasikhin; Fatkurroji (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2024)
Abstract: Knowledge and science have an important role in Islamic and Western religious views, but with different perspectives. In Islam, the Qur'an and Hadith emphasize the importance of knowledge, which is considered a spiritual and practical heritage for humanity. In the West, science is considered to be attainable through reason and empirical experience, without recognition of revelation. The research method used in this article is a comparative approach between Islamic and Western philosophical thought, especially in the fields of ontology and epistemology. An in-depth analysis of classical texts and related philosophical works is carried out to identify fundamental similarities and differences between the two traditions of thought. In Islam, knowledge comes from Allah SWT and is revealed through the revelation of the Qur'an. Islamic ontology includes the nature of the existence of Allah SWT, the universe, humans, and the relationship between the two. Meanwhile, Islamic epistemology recognizes reason, senses and revelation as sources of knowledge. On the other hand, in the Western view, science is limited to empirical reality that can be observed and measured. The ontology of science in the West emphasizes material-empirical reality, with epistemology emphasizing reason and human sensory experience as sources of knowledge. Differences in conceptions of truth are also reflected in Islamic and Western views. Islam associates truth with revelation and spiritual understanding, while the West tends more towards reason and empirical experience. Thus, although Islam and the West have different views on the sources and nature of knowledge, both have an important role in understanding the world and developing human thought.